Changes in systolic time intervals in acute myocardial infarction. Issue 6 (November 1970) - Samson, R
Abstract : After acute myocardial infarction there is a shortening of the QS2 interval and the ejection time. The pre-ejection time is either normal or prolonged. After the stage of maximum shortening of the QS2 interval and ejection time, there is a progressive improvement towards the normal. In this study there was no correlation between the shortened QS2 interval and ejection time, and the level of urinary catecholamine excretion. The physiological and clinical significance of these changes in the systolic time intervals and their relation to the altered haemodynamics and mechanics are discussed.